2021
DOI: 10.1088/1755-1315/674/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

Purse seine productivity in Lhok Pawoh fishing port, Sawang, South Aceh

Abstract: The capability of catching from fishing gear can be known from the fishing productivity. The purpose of this study was to calculate the productivity of purse seine vessels in the Fishing Port of Lhok Pawoh, Sawang, South Aceh. This research was conducted from June 10th to July 10th 2019. The method used was a census method by collecting some data such as number of fishing trip (during 2018), species and number of catches, and specification of 15 units of purse seine at Lhok Pawoh fishing port, then the data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Estimated b values from both locations were higher than three as the threshold value, which indicated a positive allometry growth pattern (i.e., the incremental weight gain is more significant than its length). The similarities were likely caused by the indifferences in gear used, whereas Rahmah et al (2021); Rizwan et al (2014); Yusuf et al (2020) all confirmed that fishers from Sibolga and Kutaraja use almost identical purse seine configurations (including its mesh size). Thus, it's generated in a reasonably consistent catch size across the year of observations due to selectivity constraint, as shown in Table 1.…”
Section: Length Distributionmentioning
confidence: 96%
“…Estimated b values from both locations were higher than three as the threshold value, which indicated a positive allometry growth pattern (i.e., the incremental weight gain is more significant than its length). The similarities were likely caused by the indifferences in gear used, whereas Rahmah et al (2021); Rizwan et al (2014); Yusuf et al (2020) all confirmed that fishers from Sibolga and Kutaraja use almost identical purse seine configurations (including its mesh size). Thus, it's generated in a reasonably consistent catch size across the year of observations due to selectivity constraint, as shown in Table 1.…”
Section: Length Distributionmentioning
confidence: 96%
“…Purse seine fisheries generally catch pelagic fish [2][3][4][5][6][7][8]. Fish that are the target of the purse seine fishery are pelagic fish that form schools that gather on fishing aids (fish agregating device of iron pontoons).…”
Section: Introductionmentioning
confidence: 99%
“…The need for electric power to support the auxiliary system on the 180 GT purse seine boat is 120 kW (150 kVA). From the need for electricity to support fishing operations, two units of electric generators were installed [14].…”
mentioning
confidence: 99%